2012
DOI: 10.3329/birdem.v2i1.12355
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Electrolyte Imbalance in Hospitalized Diabetic Patients: Experience in a Tertiary Care Hospital

Abstract: Pattern of Electrolyte Imbalance in Hospitalized DiabeticPatients 22% were on oral anti-diabetic agents and 6% were on medical nutrition therapy. Among the co-morbidities, hypertention was the most prevalent (61%), followed by ischaemic heart disease (24%), chronic kidney disease (21%), dyslipidaemia (8%) and fatty liver (4%). Diabetic peripheral neuropathy was present in 41% cases, nephropathy in 13% cases and retinopathy in 12% cases. Over all 78% (100 patients had electrolyte imbalance out of 128 patients) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 17 publications
4
12
0
Order By: Relevance
“…It was 61% in a study conducted in Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM). 28 The most common precipitating factor for hypokalemia found in our study was vomiting (63.2%). In addition to gastrointestinal loss by vomiting there is also excess renal K + loss due to metabolic alkalosis following chloride loss secondary to vomiting.…”
Section: Discussionsupporting
confidence: 45%
“…It was 61% in a study conducted in Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM). 28 The most common precipitating factor for hypokalemia found in our study was vomiting (63.2%). In addition to gastrointestinal loss by vomiting there is also excess renal K + loss due to metabolic alkalosis following chloride loss secondary to vomiting.…”
Section: Discussionsupporting
confidence: 45%
“…This cross sectional study showed that hyponatremia was the most common (63.3%) type of EI in admitted diabetic patients. It was found to be 80% in a study conducted in one of the largest hospital of Bangladesh mainly for diabetes care named Bangladesh Institute of Research & Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) 19 . Other studies have also shown that hyponatremia is common in hospitalized patients and is responsible for increased morbidity and mortality [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients in our study had multiple co-morbid conditions of which hypertension was the most common (66%). It was found to be 61% by a study conducted in BIRDEM 19 . Another study also revealed hypertension to be the most common (69%) comorbid condition in patients with hyponatremia 26 .…”
Section: Precipitating Factorsmentioning
confidence: 95%
See 2 more Smart Citations